Prevalence of Refractive Error and Color Blindness among the Inter-state Truck Drivers - Slathia, Anjali; Dhar, Renu Hashia; Mahajan, Pallavi (Highlights on Medicine and Medical Science Vol. 1, 2021)
Introduction: Road traffic incidents have increased dramatically in developing countries like India over the last two decades. Driving has evolved into a visually demanding activity that necessitates a combination of sensory (primarily visual), mental, and compensatory abilities. A medical certificate from a registered medical practitioner is sufficient to qualify for a driving licence, according to the Motor Vehicles Act of 1988 and the Central Motor Vehicles Rules of 1989. Highway accidents are most risky for truck drivers. This may be due to a variety of factors, but blurred vision is one of the most common causes of mishaps. This research was conducted to determine the ocular status of interstate truck drivers due to the significance of good vision. Aim and Objectives: Prevalence of refractive error and color blindness among interstate truck drivers was assessed. Materials and Methods: A study was conducted in Jammu, India, in collaboration with Indian Oil Corporation, in which 140 interstate truck drivers were included. Snellen's and E-chart (in the case of illiterates) and Ischiara pseudochromatic plates were used to assess the respondents' visual acuities and colour vision. The respondents' eyes were examined using a torch and a clear ophthalmoscope. On the spot, a presbyopic correction was made. All patients with ocular problems were referred to Deptt of Ophthalmology, ASCOMS for further examination. Results: In all 140 drivers were examined out of which 116(82.8%) were found to have visual acuity 6/6(normal vision) while 24(17.14%) drivers had refractive errors. 12 of the 24 truck drivers with refractive errors were found to have hypermetropia, 9 were found to have myopia, and 3 were found to have astigmatism. There was no colour blindness among the drivers. Presbyopia was discovered in 74 (52.8 %) of drivers, regardless of refractive error. Conclusion: The majority of the truck drivers with poor vision were between the ages of 41 and 50. As a result, drivers in this age group should be checked regularly for visual defects and advised to wear corrective spectacles in order to maintain normal visual acuity. Furthermore, truck drivers should have routine eye exams to detect any further deterioration of visual acuity.